DESIGNING GRAMMAR INSTRUCTION BASED ON INTEGRATED CONSCIOUSNESS-RAISING ACTIVITIES - Veni Roza (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
The paper is a theoretical framerwork on presents how to design grammar instruction by applying integrated consciousness raising activities. There are mountains of evidence that many learners, of whatever age or tendency in learning style, are unable to transfer good formal knowledge of grammar to effective use. Such discrepancy between knowledge and putting it to use had led us to look for alternative ways of helping teachers to manage the practice of grammar in a more efficient way. One possible way to do this is by using consciousness-raising activities integrated to the English skills; such as reading and writing. These activities provide students with the opportunity to interactively solve grammar tasks in a communicative way. It is hoped the model will be effective in increasing students' knowledge and in providing authentic opportunities for communication.